2016
DOI: 10.1155/2016/9545861
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Sialometaplasia of the Hard Palate in a Patient Treated with Topical Nonsteroidal Anti-Inflammatory Drug

Abstract: Necrotizing sialometaplasia is a rare, benign, self-limiting, necrotizing process involving the minor salivary glands, mainly the mucoserous glands of the hard palate. It is thought to be the result of an ischemic event of the vasculature supplying the salivary gland lobules. Some predisposing factors such as smoking, use of alcohol, denture wearing, recent surgery, traumatic injuries, respiratory infections, systemic diseases bulimia, and anorexia have been described. Herein we present a case of necrotizing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Such ischemic process may be induced by direct trauma (Birkholz et al, ; Brannon et al, ; Giles, ), local anesthetics (Brannon et al, ; Grillon & Lally, ; Shigematsu, Shigematsu, Noguchi, & Fujita, ), topical treatment with non‐steroidal anti‐inflammatory drugs (Gatti, Broccardo, Poglio, & Benech, ), cocaine abuse (Alfaya et al, ; Close & Cowan, ), radiation (McCullough, Rye, & Redman, ), alcohol (Brannon et al, ; Dunlap & Barker, ), tobacco smoking (Anneroth & Hansen, ; Brannon et al, ), upper respiratory tract infections, allergy (Brannon et al, ; Samit, Mashberg, & Greene, ), oral intubation (Romagosa et al, ), and surgical procedures (Batsakis & Manning, ). Mandel and co‐workers described a patient with NS resulting from impaired blood supply due to sickle‐cell anemia (Mandel, Kaynar, & DeChiara, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such ischemic process may be induced by direct trauma (Birkholz et al, ; Brannon et al, ; Giles, ), local anesthetics (Brannon et al, ; Grillon & Lally, ; Shigematsu, Shigematsu, Noguchi, & Fujita, ), topical treatment with non‐steroidal anti‐inflammatory drugs (Gatti, Broccardo, Poglio, & Benech, ), cocaine abuse (Alfaya et al, ; Close & Cowan, ), radiation (McCullough, Rye, & Redman, ), alcohol (Brannon et al, ; Dunlap & Barker, ), tobacco smoking (Anneroth & Hansen, ; Brannon et al, ), upper respiratory tract infections, allergy (Brannon et al, ; Samit, Mashberg, & Greene, ), oral intubation (Romagosa et al, ), and surgical procedures (Batsakis & Manning, ). Mandel and co‐workers described a patient with NS resulting from impaired blood supply due to sickle‐cell anemia (Mandel, Kaynar, & DeChiara, ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Trauma from intubation procedure for general anesthesia also can result in necrotizing sialometaplasia, bulimia nervosa, an eating disorder with marked binge eating followed by purging [ 3 , 4 ]. Gatti A et al described a necrotizing sialometaplasia caused by excessive use of the nonsteroidal anti-inflammatory drug Flurbiprofen oral spray that contained alcohol six times once a day for five weeks for prevention of sore throat [ 5 ]. Senapati S et al reported its occurrence due to immune-mediated vasculitis such as granulomatosis with polyangiitis Wegener’s disease [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter leads to infarction of the minor salivary gland acini with necrosis, in ammation, and salivary duct metaplasia 4 . Numerous risk factors have been described to explain the onset of local ischemia in the minor salivary glands of the hard palate 5 . Smokers reportedly have a higher prevalence of palatal lesions 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of necrotizing sialometaplasia does not require surgery 5 . The treatment of this lesion is avoidable due to its tendency for spontaneous healing and depends on whether the lesion is symptomatic 7 .…”
Section: Discussionmentioning
confidence: 99%